Magnocellular training improves visual word recognition - Chouake, Tara; Levy, Tamar; Javitt, Daniel C.; Lavidor, Michal (Frontiers in Human Neuroscience, 2012)
Current research has shown that the magnocellular system may play a crucial role in reading deficits related to dyslexia. The current study explored the relationship between magnocellular activity and reading abilities; we examined the hypothesis that a repeated usage of the magnocellular stream may improve reading by strengthening crucial neural pathways. Visual training was conducted for five consecutive days using a motion detection task (magnocellular training) and a control task of pattern detection (parvocellular training). Reading abilities of skilled readers were measured before and after the training using a lexical decision task. It was found that low grade visual training overall can improve speed of lexical decision, but only magnocellular training selectively improved accuracy. Improvement in the magnocellular training task predicted performance on adjacent anagram and word recognition after training. In contrast, in the control group (parvocellular training) degree of improvement in training did not predict lexical decision performance after training. This result lends support to the role of the magnocellular system in reading, and has potential implications for neuro-rehabilitation of reading related deficits.